1978
DOI: 10.1902/jop.1978.49.7.351
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Localized Gingival Recessions: Part I. Lateral Sliding Flap

Abstract: This study was undertaken to evaluate biometrically the changes that occur on the recipient as well as on the donor tooth with regard to gingival recession, sulcus depth and width of keratinized gingiva after performing a lateral sliding flap in the treatment of localized denuded roots. Fourteen teeth with gingival recession were treated using a lateral sliding flap. Measurements were recorded preoperatively and 1, 3 and 6 months after surgery. A mean gain of 2.69 mm of soft tissue coverage over the denuded ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
3

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 11 publications
0
50
0
3
Order By: Relevance
“…When more than one study reported follow-up data on the same patients, 45,46,65,69,70 we reported the data extracted from the most recent study; in one study, 65 we chose the shorter follow-up because it covered a larger number of patients.…”
Section: Data Collectionmentioning
confidence: 99%
“…When more than one study reported follow-up data on the same patients, 45,46,65,69,70 we reported the data extracted from the most recent study; in one study, 65 we chose the shorter follow-up because it covered a larger number of patients.…”
Section: Data Collectionmentioning
confidence: 99%
“…The methodology used and the results obtained with the individual techniques have been reported separately. 3,6 All data obtained were analyzed statistically to deter mine the significance of the results after the use of the lateral sliding flap and the coronally repositioned flap. The results with both techniques were compared to test the following hypotheses:…”
mentioning
confidence: 99%
“…Furthermore, other subsequent modifi cations and standardisations of technique by Bjorn [ 69 ], Smukler [ 70 ], Patur [ 71 ], Guinard and Caffesse [ 72 ], Leis and Leis [ 73 ], Bahat et al [ 74 ], Milano [ 75 ] and more recently Zucchelli et al [ 76 ] were proposed either to improve the characteristics of the fl ap or to provide better protection to the donor areas. In addition, with the development and results of other techniques after the mid-1980s, especially those involving the use of subepithelial connective tissue grafts, soft tissue substitutes and guided tissue regeneration combined with coronally advanced fl ap procedures, the scientifi c community seems has lost interest in the evaluation of LPF.…”
Section: Historical Notementioning
confidence: 99%